Implementasi Algoritma Floyd Warshall Untuk Pencarian Rute Terpendek Berbasis Android (Studi Kasus : Pandu Logistik Kuningan) - Panji Novantara; Fitri Susanti (Universitas Kuningan, 2019)
Advance of technology and information makes business developments in the online store in Indonesia increased. This phenomenon is clearly illustrated in demand and market movements in the online world that is growing every day. The continued development of this online store business will affect the development of logistics business in Indonesia. The growth of the logistics business has now been evenly distributed throughout Indonesia. Therefore, the development of online business is a great opportunity that is very promising for the delivery service company. In the case of the distribution of goods from companies logistik, determiningthe shortest path from one point to another is a problem frequently encountered in the distribution of goods as well as everyday life.Along with the elapsed time and also the development of science and technology, the problem of finding the shortest path has been solved by various algorithms. One of them is the Floyd Warshall algorith. Making thisandroid based software so that employees can access the application anywhere and anytime by using internet connection. The software has a web service as a service provider and operator for the update process on the admin side.The design of the system uses an objectbased design by using the Unified Modelling Language (UML)method. This application is expected to assist in finding the shortest route to distribute of goods to the consumers.Keywords: logistics business, online business, shortest path, Floyd Warshall algorith, UML